2022
DOI: 10.3390/su14159684
|View full text |Cite
|
Sign up to set email alerts
|

Current Status and Future Perspectives of Carbon Pricing Research in Austria

Abstract: In the context of the European Green Deal, the European Commission and the European Parliament proposed to intensify Europe’s ambition for its 2030 climate targets. In the case of Austria, the current government set itself the goal of being carbon neutral by 2040. The Federal Chancellery of Austria also presented a plan to introduce a carbon price for emissions from the non-EU ETS; a task force is underway to launch a formal proposal in 2022, and thus it is relevant to investigate the present stage of scientif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 97 publications
0
2
0
Order By: Relevance
“…Bibliometric analysis can be used to assess research trends, the most relevant topics in a research corpus, and the collaborative networks formed among different authors [65][66][67][68][69][70]. In recent years, bibliometrics has been used in mainstream country-level analyses of development capacity and scientific and technological policy [71][72][73][74][75]. This trend has led to expanded bibliometric data collection in regard to various countries, research institutions, and scientific fields and the development of indicators as an essential basis for formulating or reviewing policies [76].…”
Section: Methodsmentioning
confidence: 99%
“…Bibliometric analysis can be used to assess research trends, the most relevant topics in a research corpus, and the collaborative networks formed among different authors [65][66][67][68][69][70]. In recent years, bibliometrics has been used in mainstream country-level analyses of development capacity and scientific and technological policy [71][72][73][74][75]. This trend has led to expanded bibliometric data collection in regard to various countries, research institutions, and scientific fields and the development of indicators as an essential basis for formulating or reviewing policies [76].…”
Section: Methodsmentioning
confidence: 99%
“…Practice has also shown that the futures price of the EU carbon market can predict and prevent carbon price risks well [29]. Santos et al found that, even though the Austrian government presented a plan to introduce a carbon price, there are still uncertainties about the design of the carbon pricing instrument, the institutional and regulatory framework, revenue recycling policies, the impacts on sectoral GDP, the competitiveness indicators, and international trade; meanwhile, the transport sector should require special attention in terms of mitigation and adaptive measures [41].…”
Section: The Influencing Factors Of the Ctpmentioning
confidence: 99%